THE ROLE OF MANAGEMENT IN THE ESTABLISHMENT OF NOBLE CHARACTER OF STUDENTS (Qualitative Study at SMPN Satap 1 and SMPN 3 Jatisari, Karawang District) - Maksum, Musahar; Sanusi, Achmad; Makmun, Tb. Abin Syamsudin; Fatkhullah, Faiz Karim (AGUSPATI Research Institute, 2022)
This research is motivated by the still occurrence of juvenile delinquency at the first school age due to the weak cultivation of noble character values through the school curriculum. The research was conducted to obtain an overview of the role of management in shaping the noble character of students which was studied based on planning, organizing, implementing, supervising, inhibiting factors and improvement efforts. This study uses a descriptive method with a qualitative approach through interview, observation and documentation studies. The results of the study indicate that the role of management in the formation of the noble character of students can give meaning to the concept of managing educational and learning activities through planning, organizing, implementing, and supervising, but to achieve the appropriate goals, it is expected that there are still obstacles in the availability of infrastructure, abilities and sincerity of the students. educators, and the lack of school cooperation with related external parties. Thus, to achieve this character requires the support of school resources, the involvement of family, community and local government in carrying out sustainable noble character development.